PENERAPAN APLIKASI ANDROID UNTUK ALAT MONITORING KESEHATAN MANUSIA - Kevin; joni eka candra (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2023)
The purpose of this research is to realize an Android-based human health condition monitoring tool, to combine Pulse sensors, DS18B20 temperature sensors and sound sensors as a tool for monitoring Android-based human health conditions, to provide new alternatives for the procurement of more health monitoring tools. cheap. The objects to be measured are 3 indicators, namely measurement of heart rate, body temperature, and breathing which input data through DS18B20 temperature sensor, Pulse sensor, Sound sensor. For measurement of heart rate and respiration measurements are carried out for 1 minute. The measurement results will be displayed on the LCD then the measurement data will be sent to the Android application via Bluetooth HC-05. The results of the study through later measurements were compared with manual measurements and using a thermometer for measuring body temperature. Based on the research data it can be concluded that all the circuits are going well, there are small differences between the measurement results manually or with a thermometer with measurements using research tools, the percentage of temperature sensor error DS18B20 0.33%, Pulse sensor 2.46%, Sound sensor 4.84% so that this tool can be a measuring tool for health monitoring. This tool is expected to be further developed by combining other health indicators.